Treatment of patients with transposition of great arteries and pulmonary vascular obstructive disease. Issue 3 (March 1978) - Byrne, J; Clarke, D; Taylor, J F; Macartney, F; de Leval, M; Stark, J
Abstract : Twenty-two patients with transposition of the great arteries with or without ventricular septal defect and one with double outlet right ventricle, d-malposition, and severe pulmonary vascular obstructive disease were treated surgically. All were cyanosed and had very limited exercise tolerance. Preoperatively, systemic arterial oxygen saturation (SaO2) varied from 45 to 79% (mean 65), haemoglobin was 13 to 23 g/dl (mean 19). Pulmonary arteriolar resistance was 6.4 to 35 units m2 (mean 17). In the patients with a ventricular septal defect the Mustard operation was done without closure of the ventricular septal defect, and in the 3 patients with intact ventricular septum the Mustard operation was combined with creation of a ventricular septal defect. All patients survived the operation and improved. Postoperative SaO2 ranged from 75 to 96% (mean 89) and haemoglobin from 10.6 to 17.8 g/dl (mean 14.0). This improvement was significant (P less than 0.05). Five patients have had a postoperative cardiac catheterisation. The pulmonary arteriolar resistance remains high in all. Postoperative follow-up varies from 4 to 40 months (mean 14 months). So far there have been no late deaths and all patients remain improved.